Fatigue and tribological properties of plastics and elastomers - McKeen, Laurence W. (PDL handbook series., 2010)
Part of a series of core databooks within the William Andrew 'Plastics Design Library', Fatigue and Tribological Properties of Plastics and Elastomers provides a comprehensive collection of graphical multipoint data and tabular data covering fatigue and tribology. The concept of fatigue is very straightforward: if an object is subjected to a stress or deformation, and it is repeated, the object becomes weaker; this weakening of plastic material is called fatigue. Tribology is the science and technology of surfaces in contact with each other and therefore covers friction, lubrication and wear. The reduction of wear and fatigue, and improvement of lubrication are key bottom-line issues for engineers and scientists involved in the plastics industry and product design with plastics. Fatigue and Tribological Properties of Plastics and Elastomers, 2nd Edition is an update of all that has changed in the world of plastics since the 1st edition appeared nearly 15 years ago, and has been reorganized from a polymer chemistry point of view. A hard-working reference tool: part of the daily workflow of engineers and scientists involved in the plastics industry and product design with plastics The reduction of wear and fatigue, and improvement of lubrication are key bottom-line issues. The data in this book provides engineers with the tools they need to design for low failure rates.